2020
DOI: 10.3390/ijms21165856
|View full text |Cite
|
Sign up to set email alerts
|

New Anti SARS-Cov-2 Targets for Quinoline Derivatives Chloroquine and Hydroxychloroquine

Abstract: The rapid spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has created a severe global health crisis. In this paper, we used docking and simulation methods to identify potential targets and the mechanism of action of chloroquine (CQ) and hydroxychloroquine (HCQ) against SARS-CoV-2. Our results showed that both CQ and HCQ influenced the functionality of the envelope (E) protein, necessary in the maturation processes of the virus, due to interactions that modify the flexibility of the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 114 publications
0
30
1
Order By: Relevance
“…Flexible ligand docking experiments, successfully used in our previous work [ 31 , 59 , 60 , 61 , 62 , 63 , 64 ], were performed employing AutoDock 4.2.6 software implemented in YASARA (v. 20.10.4, YASARA Biosciences GmbH, Vienna, Austria) [ 65 , 66 ], using the three-dimensional crystal structure of hCoV-229E M pro (PDB ID: 1P9S), the three-dimensional crystal structure of SARS-CoV-2 M pro in complex with an inhibitor N3 PRD_002214 (PDB ID: 6LU7), both obtained from the Protein Data Bank (PDB, ), and the Lamarckian genetic algorithm (LGA). The covalent bond between the Cys145 residue and the crystallized ligand has been eliminated.…”
Section: Methodsmentioning
confidence: 99%
“…Flexible ligand docking experiments, successfully used in our previous work [ 31 , 59 , 60 , 61 , 62 , 63 , 64 ], were performed employing AutoDock 4.2.6 software implemented in YASARA (v. 20.10.4, YASARA Biosciences GmbH, Vienna, Austria) [ 65 , 66 ], using the three-dimensional crystal structure of hCoV-229E M pro (PDB ID: 1P9S), the three-dimensional crystal structure of SARS-CoV-2 M pro in complex with an inhibitor N3 PRD_002214 (PDB ID: 6LU7), both obtained from the Protein Data Bank (PDB, ), and the Lamarckian genetic algorithm (LGA). The covalent bond between the Cys145 residue and the crystallized ligand has been eliminated.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of the structures of the molecules and the protein and all parameters for docking experiments and molecular dynamics simulations were conducted following the procedures previously reported by us [ 14 , 15 , 16 , 27 , 34 ]. The 3D structures of the BoNT LC/A−G (PDB ID: 4HEV, 1F82, 2QN0, 2FPQ, 1T3A, 2A8A, and 1ZB7) used for the experiments were obtained from the Protein Data Bank.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, CAMD and computational chemistry are essential aspects of drug design and have been used to follow atom-by-atom interaction and reactivity [ 11 , 12 ]. From hit identification to lead optimization and beyond, approaches such as structure-based, ligand-based, and virtual screening are widely used by our research group to support drug discovery efforts [ 13 , 14 ]. Generally, these methods can be divided into structure-based and ligand-based drug design.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, modeling of the SARS-CoV-2 NSP14 active site revealed that remdesivir would create a steric clash, suggesting a less efficient excision of this drug [ 124 ]. Gentile et al proposed that chloroquine and hydoxychloroqiune could interact in the ExoN and SAM-MTase activity site [ 125 ]. SARS-CoV-2 NSP10 and NSP16 mutations were detected in some patients and in silico models suggest that it could have an impact on the stability of the complex [ 116 , 126 ].…”
Section: Structure and Function Of The Sars-cov-2 Rna Polymerase: Thementioning
confidence: 99%